Processed physical properties measured on sediment core GeoB22353-2 - Kai-Frederik Lenz; Calvin Campbell; Andrea Catalina Gebhardt; Tarik Bozkuyu (PANGAEA, 2025)
Sound knowledge about the petrophysical characteristics of a sediment core is a prerequisite for any subsequent paleoenvironmental study relying on sediment proxies. Physical properties of whole-round sediment cores are acquired as a first step of sediment core description, prior to slicing of sediment cores into two halves. Here, we present processed physical-properties data of core GeoB22353-2 acquired with a Geotek MSCL-S system on the unsplit core, retrieved RV Maria S. Merian expedition MSM66 WESTBAFF to the Baffin Bay, Canada/Greenland, in 2017. Cores were processed according to the standard protocol given by the manufacturer Geotek Ltd.